How Does AI Handle Rare Diseases in Medical Imaging? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2016)
The diagnosis of rare diseases presents a formidable challenge to the medical community. With over 7,000 identified rare diseases affecting approximately 1 i...
Keywords: AI in Medical Imaging and Diagnostics; Handle; Diseases; Medical; Artificial Intelligence; Machine Learning; Deep Learning